Landscape‐scale biodiversity governance: Scenarios for reshaping spaces of governance. (21st January 2019) - Leventon, Julia; Schaal, Tamara; Velten, Sarah; Loos, Jacqueline; Fischer, Joern; Newig, Jens
Abstract: In this paper, we present an alternative governance system for managing biodiversity in agricultural landscapes. Focusing primarily on the European Union (EU), we start with the premise that there is a need to rethink biodiversity governance to bring together land managers for collaboration and to close mismatches between levels of governance and ecological scales. We therefore create four archetypal governance scenarios that represent hypothetical extremes in two variables. The first variable is the scale of governance and differentiates between a primary focus on administrative units (e.g., country, state, and county) versus ecological scales (bioregion and landscape). The second variable is the degree of decentralization and devolution and differentiates between a top‐down, central‐state system, versus a bottom‐up, broad actor‐network system. On the basis of their considered strengths and weaknesses, we present a hybrid scenario as our proposed alternative governance system. This system brings together decision makers, land managers, and a broader range of stakeholders at a landscape scale to plan biodiversity goals and actions. This, in turn, will more closely match the biophysical conditions for effective biodiversity conservation than existing EU approaches, without overly increasing the administrative burden.